Synthesis Of Zinc-Aluminium-Hippurate Nanocomposite By Various Methods. - Abdul Bahar, Faiza (2009)

(untitled)
Zinc-aluminium-layered double hydroxide (ZAL) with nitrate as counter anion was prepared by direct co-precipitation method at constant pH, 7.5 under N2 (g) atmosphere. The anion of hippuric acid (HA), as an organic guest was chosen to be intercalated into the interlayers of Zn-Al-layered double hydroxide (ZAL) inorganic host by direct coprecipitation method for the formation of Zn-Al-hippurate nanocomposite (ZAH), a hostguest type of material. Various parameters, such as Zn to Al initial molar ratios, Ri which are 2, 3, 4, 5 and concentrations of hippurate anion in a range of 0.06 to 0.15 M, have been studied for the formation of Zn-Al-hippurate nanocomposite synthesised by direct coprecipitation method (ZAHDM). X-ray diffraction pattern shows expansion of the precursor basal spacing compared to ZAL in order to accommodate the hippurate anion, which is larger in size than the nitrate. ZAHDMs synthesised at 0.15 M HA for all the ratios were chosen for further characterizations because sharper, symmetrical and more intense peaks were observed for these samples compared with samples prepared with other concentrations. In this study, ZAHs was also prepared by indirect anion exchange method (ZAHXMs) and reconstruction method (ZAHRMs). The nanocomposites prepared by these different methods show that the highest basal spacing values were observed for the nanocomposite synthesis by direct coprecipitation method (ZAHDMs) and the lowest were obtained by using anion exchange method (ZAHXMs). This shows that different crystalline structure was observed for the different method of synthesis of the nanocomposites. The final ratio, Rf value for ZAHDM and ZAHRM nanocomposites were near to its initial molar ratio, Ri but for ZAHXMs (synthesis by anion exchange method), the Rf obtained are only in the range of 0.90 – 1.72 compared to their Ri of 2 – 5. The BET specific surface area values obtained for ZAHXM also show the lowest value compared to ZAHDM and ZAHRM nanocomposites. These show that the method of synthesis also plays the role in determining the resulting properties of the nanocomposites. For ZAHDMs and ZAHXMs nanocomposites, the accumulated release profile of HA from the interlayer of the nanocomposite in a sodium aqueous solution were studied and values of the percentage release were obtained by separately put each of the nanocomposite into the sodium carbonate aqueous solutions at various concentrations of 0.0025, 0.005 and 0.01 M. The release rate of HA was found to be faster for nanocomposite prepared by indirect anion exchange method, compared to the one synthesised by direct co-precipitation method. The data of the HA released from the nanocomposites into various aqueous carbonate solutions were then fitted into various models of release kinetics. In which, the release of the intercalated guest for both ZAHDM and ZAHXM were found to be governed by pseudo-second order kinetic.